Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1557/opl.2012.1209
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multimedia and Activity-Based Supplemental Teaching Resources in Materials Science Education

Abstract: A comparative study investigating the integration of supplemental teaching resources in materials science education was developed for the purpose of determining the effectiveness of teaching strategies. Digital stories created by students, excerpts from the Nova Making Stuff documentaries, YouTube educational videos and student generated demo-kits were used as part of the investigation whereby two 9th grade science classes (n~26) were evaluated. Each participant in the study received one period (40-min) of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The students in the experimental group reported they were more prepared than those in the control group even though they prepared in advance less for class. This supported the findings of several researchers (Day et al, 2012;Dong et al, 2012;Green et al, 2012;Jordan et al, 2010, Kao, 2008Ruthven, 2012) who note videos and supplemental information can be beneficial. The students also agreed an appropriate number of videos were provided.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The students in the experimental group reported they were more prepared than those in the control group even though they prepared in advance less for class. This supported the findings of several researchers (Day et al, 2012;Dong et al, 2012;Green et al, 2012;Jordan et al, 2010, Kao, 2008Ruthven, 2012) who note videos and supplemental information can be beneficial. The students also agreed an appropriate number of videos were provided.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, class lectures that were previously delivered once in the classroom can be viewed over and over again by students to assimilate the material. Day et al (2012) found multimedia education can be effective in science as supplementary resources. According to Jordan, Pakzad, and Oats (2010) students in engineering should be "encouraged to expand their knowledge of the material being taught through media, images, animation and streaming audio/video" (p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%